Status and perspectives on 100% renewable energy systems. (15th May 2019) - Hansen, Kenneth; Breyer, Christian; Lund, Henrik
Abstract: This article shows that research in the design of 100% renewable energy systems in scientific articles is fairly new but has gained increasing attention in recent years. In total, 180 articles published since 2004 have been identified and analysed. Many of these articles have a predominant focus on the electricity sector. However, an increasing number of studies apply a cross-sectoral holistic approach on the entire energy system. Most studies analyse energy systems for the final 100% renewable state, while a small, though increasing, number also investigate energy transition pathways; how to reach the target. Europe, and thereafter the US and Australia, are well researched, while other parts of the world lack behind, and there is a focus on individual country studies. Henceforward, there is a need for applying a cross-sectoral holistic approach as well as coordinating individual country studies with the global context. Highlights: Research in design of 100% renewable energy has increased. Energy is the leading forum for 100% RES research. Holistic cross-sectoral analysis is becoming state-of-the-art. There is a future need for linking the local and the global level.